Molecular Mechanisms and Therapeutic Effects of (−)-Epicatechin and Other Polyphenols in Cancer, Inflammation, Diabetes, and Neurodegeneration. (9th June 2015) - Shay, Joseph; Elbaz, Hosam A.; Lee, Icksoo; Zielske, Steven P.; Malek, Moh H.; Hüttemann, Maik
Abstract : With recent insight into the mechanisms involved in diseases, such as cardiovascular disease, cancer, stroke, neurodegenerative diseases, and diabetes, more efficient modes of treatment are now being assessed. Traditional medicine including the use of natural products is widely practiced around the world, assuming that certain natural products contain the healing properties that may in fact have a preventative role in many of the diseases plaguing the human population. This paper reviews the biological effects of a group of natural compounds called polyphenols, including apigenin, epigallocatechin gallate, genistein, and (−)-epicatechin, with a focus on the latter. (−)-Epicatechin has several unique features responsible for a variety of its effects. One of these is its ability to interact with and neutralize reactive oxygen species (ROS) in the cell. (−)-Epicatechin also modulates cell signaling including the MAP kinase pathway, which is involved in cell proliferation. Mutations in this pathway are often associated with malignancies, and the use of (−)-epicatechin holds promise as a preventative agent and as an adjunct for chemotherapy and radiation therapy to improve outcome. This paper discusses the potential of some phenolic compounds to maintain, protect, and possibly reinstate health.